Geography teachers from the perspective of special and inclusive educacion - Brinco, Lucian Armindo da Silva (Revista Ensino de Geografia (Recife), 2021)
The aim of this study is to analyze the experiences, perceptions and / or perspectives of teachers of geography in relation to aspects of special and inclusive education. As the development of the same occurs during the coronavirus pandemic (COVID-19), online resources are used to obtain the answers of six (6) teachers, who teach in schools in the central region of the State of RS. Thus, the results show that, in general, they do not feel able to work from the perspective of schooling students with Special Educational Needs (NEEs), given the time of their academic training. Only one (1) teacher is also involved in continuing education courses in the area of special education. They also state that the facilities for school inclusion fall on family support and Specialized Educational Assistance (AEE), and the difficulties arise from their lack. Finally, they emphasize that there are many issues, whether in the context of educational policies or in the teaching and learning system as a whole, which need to be reevaluated, so that students with NEEs feel, in fact, included